Population Structure of Bigeye Tuna (Thunnus obesus) Of Indian Ocean Based on Microsatellite DNA Analysis - Batti, Andi Bahtiar; Pharmawati, Made; Mahardika, I Gusti Ngurah Kade (Metamorfosa: Journal of Biological Sciences, 2020)
Bigeye tuna ( Thunnus obesus ) is a main commodity for international markets of tuna fisheries in Indonesia, resulting in an increasing tuna capturing across Indian Ocean; Therefore, improvements in management and catchment are needed for tuna sustainability, such as a better understanding in its population structures. 30 fins tissues of bigeye tuna in total, were collected from two parts of Indian Ocean, (western Sumatra and southern Nusa Tenggara) during 20 December 2015 until Mei 2016. This study was aimed to gain some information on population structures of bigeye tuna of Indian Ocean based on microsatellite analysis. DNA analysis were conducted in a laboratory of Institute of Marine Research and Development, Gondol, Bali, Indonesia and the 1 st Base -Singapore. The benefit of this study is to provide data and information on population structures of bigeye tuna of Indian Ocean. The results of Analysis of Molecular Variance (AMOVA) indicated that populations of bigeye tunas captured from the two fishing areas are included in one population.